Possibilities for improving the effectiveness of IVF programs in «difficult» patients - E. B. Rudakova; T. V. Strizhova; E. A. Fedorova; L. Yu. Zamakhovskaya (Лечащий Врач, 2021)
The best results of in vitro fertilization (IVF) and embryo transfer programs are observed in patients younger than 35 years old with tubo-peritoneal infertility factor in the absence of male factor. Difficulties in terms of reducing the effectiveness of IVF programs and / or the occurrence of complications arise in patients at risk for these complications, in patients of the late stage of the reproductive period and in infertility associated with certain gynecological diseases. To achieve the desired results in these groups of patients, non-standard approaches are required, which allow not only to increase the effectiveness of IVF programs, but also improve the rate of live births.